Analisis Faktor Penyebab Keterlambatan Pendistribusian Dokumen Rekam Medis ke Poli Bedah di RSUPN Dr. Cipto Mangunkusumo - Firza Azis; Atma Deharja (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Based on research at RSUPN Dr. Cipto Mangunkusumo, Central Jakarta, there was a delay in the distribution of medical record documents to arrive at the surgical clinic more than 30 minutes. The purpose of this research was to identify the causes of the delayed in the distribution of medical records documents to arrive at the surgical clinic based on 5 management elements, such as man factors, materials factors, machine factors, methods factors, motivation factors and the factors of arrange the recommendations effort for improvements in the supply of medical record documents at RSUPN Dr. Cipto Mangunkusumo. This type of the research uses qualitative analysis. Based on the results and discussion, in the man factor there are filing staffs who still lack discipline such as, often come late, the one of the filing staff often absen. The material factor there is still a medical record document which folder / cover is torn, and therefore the medical record number and the patient's name are not visible or unclear, so that the staffs has trouble when searching for the medical record documents. The machine factor, which is EHR, usually occurs loading or could not be a accessed so the tracer not coming out and when the EHR can be accessed, the tracer will come out with a lot. Ther methods factor is KPI percentage of the speed of providing medical records of patients without agreement arrived at the polyclinic in 2019 still has not reached the target of 90%. After an evaluation, in 2020 the time of the document arrived at the polyclinic would be less than 30 minutes by reducing the target to 75%. Motivation factor there is no external motivation provided by the head of the medical record .The conclusion is the filing staffs did not come on time and did not come, the materials of the cover on medical record documents are easily torn, EHR is often difficult to access, the achievement level has not yet reached the target of providing medical record documents, and there is still no motivation from the head of medical record.